OC-032 Regenerative medicine for intestinal failure: demonstrating the potential for intestinal organoids to repopulate the epithelium of the intestine. (22nd June 2015) - Meran, L; Li, V; De Coppi, P
Abstract : Introduction: Irreversible intestinal failure (IF) is associated with significant morbidity and mortality. Parenteral nutrition (PN) services have improved over the last decade, yet the life expectancy of patients on PN remains far below enterally fed patients. 1 Patients suffering complications of PN are referred for intestinal transplantation however survival amongst those receiving a transplant is limited due to high graft-rejection rate, sepsis and risks of long-term immunosuppression. All these challenges reveal a persisting urgent need for new treatments for IF. Here, we present advances in our work on intestinal stem cell biology and tissue engineering that provide a realistic alternative to current available treatments for IF. Method: Ethical approval was obtained from the NRES Committee London–Bloomsbury to collect intestinal tissue from patients at Great Ormond Street Hospital. Intestinal organoids were cultured as previously described. 2 Decellularization of whole intestinal sections was performed with 2 cycles of Detergent Enzymatic Treatment (DET). 3 Organoids were cultured on epithelial surfaces of acellular matrices in vitro for 10 days before fixation. Cell survival was analysed by histology, immunofluorescence and electron microscopy techniques. Results: Three dimensional epithelial organoids were successfully cultured from endoscopic biopsies (Figure 1 ). Organoids were expanded to generate sufficient cells to repopulate the matrix at the required density. Whole sections of intestine were successfully decellularized and assessed using H&E staining and scanning electron microscopy. Organoids were seeded onto the epithelial surface of the matrices and allowed to engraft for a period of 10 days. The formation of a neo-epithelium with evidence of a microvillus brush border was evident after 10 days in culture. Furthermore, cells had successfully migrated into the crypt domains of the matrix. Conclusion: We demonstrate the potential of tissue engineering for intestinal failure by combining organoid cultures with decellularization expertise. Our results confirm intestinal organoids to be the ideal source of progenitor cells to regenerate the intestinal epithelium, with potential clinical applications for transplantation. Disclosure of interest: None Declared. References: Pironi L, Joly F, Forbes A, et al . Long-term follow up of patients on home parenteral nutrition in Europe: implications for intestinal transplantation. Gut 2011;60:17–25 Sato T, Stange DE, Ferrante M, et al . Long term expansion of epithelial organoids from human colon, adenoma, adenocarcinoma and Barrett's epithelium. Gastroenterology 2011;141(5):1762–72 Totonelli G, Maghsoudlou P, Garriboli M, et al . A rat decellularized small bowel scaffold that preserves villus-crypt architecture for intestinal regeneration. Biomaterials 2012;33(12):3401–10